BStGer SK.2023.49 vom 31. Januar 2025 - Bundesstrafgericht (2025)
Corruption passive d'agents publics étrangers (art. 322septies al. 2 CP); corruption active d'agents publics étrangers (art. 322septies al. 1 CP); corruption active d'agents publics étrangers (art. 322septies al. 1 en lien avec l'art. 102 al. 2 CP)